2020
DOI: 10.1097/adm.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resident Physicians’ Knowledge of and Attitudes Towards Prescribing Buprenorphine for Patients With Opioid Use Disorder

Abstract: Objective: To determine internal medicine (IM) residents’ knowledge of, attitudes towards, and barriers to prescribing buprenorphine for opioid use disorder (OUD). Methods: We conducted a cross-sectional study of IM residents across all 35 Accreditation Council for Graduate Medical Education (ACGME) accredited Florida IM residency programs. We used an online survey to collect information about resident demographics, substance use curriculums, career int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Since buprenorphine was approved for the treatment of OUD by the FDA in 2002, many studies have examined attitudes toward buprenorphine and prescribing practices. Studies found that knowledge about buprenorphine, exposure to its use, and attitudes about its effectiveness and acceptability in treating OUD are related to prescribing practices 64 , 72 , 87 , 91 , 94 , 95 , 110 . Certain types of physicians, especially generalist physicians and addiction specialists, tend to be more open to prescribing buprenorphine 61 , 64 , 72 , 83 , 94 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since buprenorphine was approved for the treatment of OUD by the FDA in 2002, many studies have examined attitudes toward buprenorphine and prescribing practices. Studies found that knowledge about buprenorphine, exposure to its use, and attitudes about its effectiveness and acceptability in treating OUD are related to prescribing practices 64 , 72 , 87 , 91 , 94 , 95 , 110 . Certain types of physicians, especially generalist physicians and addiction specialists, tend to be more open to prescribing buprenorphine 61 , 64 , 72 , 83 , 94 .…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly endorsed barriers to prescribing buprenorphine include inadequate access to behavioral health, counseling, and other support services; logistical issues such as patient limits, DEA involvement, scheduling, and record-keeping; lack of knowledge about OUD treatment and need for additional training; and concerns about fit with practice and potential changes to the patient mix 64 , 65 , 76 , 77 , 83 , 86 , 87 , 91 , 92 , 95 , 101 , 109 , 110 . Netherland et al 76 .…”
Section: Resultsmentioning
confidence: 99%
“…Other previously cited barriers to prescribing buprenorphine include insufficient reimbursement, lack of knowledge and expertise, lack of time or interest, and a perception that patients with OUD may be "high maintenance." [11][12][13] Some studies have identified logistical considerations surrounding prescribing including cumbersome regulations, inadequate office space and inadequately trained staff, as well as lack of institutional support and behavioral health resources. 14,15 Provider concerns about "opening the flood gates" to OUD patients and beliefs about the usefulness of MOUD have also been identified as barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Residents in primary care related specialties are also well positioned to apply learned SUD skills to their clinical practice as evaluation and management of chronic diseases other than addiction, such as diabetes and hypertension, are core to their training. Despite this clinical exposure, residency training in SUD prevention, screening, assessment, treatment and recovery is not as robust as warranted [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%